Association between femorotibial rotational mismatch and early clinical outcomes after bi-cruciate retaining total knee arthroplasty - Shine Tone; Yohei Naito; Hiroki Wakabayashi; Akihiro Sudo; Masahiro Hasegawa (BMC Musculoskeletal Disorders)
Abstract Background Bi-cruciate retaining (BCR) total knee arthroplasty (TKA) is considered to provide improved clinical function and kinematics compared with conventional TKA, but it is unclear which factors affect clinical outcomes after BCR TKA. This study aimed to investigate whether rotational alignment of the femoral and tibial components and rotational mismatch between the femoral and tibial components affected early clinical outcomes after BCR TKA, according to the 2011 version of the Knee Society Score (2011KSS). Methods This retrospective cohort study included 39 knees that underwent BCR TKA. Rotational alignment of the femoral and tibial components and rotational mismatch between the components were measured by computed tomography based three-dimensional evaluation software. 2011KSS was obtained at 3, 6, and 12 months postoperatively. The relationship of each of rotational alignment and rotational mismatch with 2011KSS was analyzed. Results Rotational alignment of the femoral and tibial components was not correlated with symptoms, patient satisfaction, patient expectations, or functional activities at 3, 6, or 12 months postoperatively. Rotational mismatch was negatively correlated with symptoms, patient satisfaction and functional activities at 3 months; negatively correlated with symptoms and functional activities at 6 months; and negatively correlated with symptoms, patient satisfaction, patient expectations and functional activities at 12 months postoperatively. Conclusions Rotational mismatch between the femoral and tibial components was negatively correlated with 2011KSS, whereas no relationship of rotational alignment of the femoral and tibial components with 2011KSS was observed. Excessive external rotation of the tibial component relative to the femoral component resulted in worse early clinical outcomes.